A glocalised higher education hub in the making? a case study of Shenzhen’s higher education space - Fang, Yuning (2025)
This thesis examines the changing nature of Chinese higher education through the case of Shenzhen as an emerging higher education hub. The spatio-institutional transformation of the sector is characterized by increasing regional disparities and uncertain educational outcomes for students. Thus, it is both timely and necessary to examine Shenzhen as a critical case study to understand the transitions and their consequences for the sector. Drawing on empirical data, the analysis focuses on three key objectives – policy frameworks, university agency, and student experiences. Based on interviews with former policymakers and university students, as well as observations from university management meetings, this research makes three main arguments: (1) Shenzhen’s higher education landscape is shaped by a locally driven funding system and the city’s status as China’s “reform pioneer”; (2) universities respond through strategic alliances with the government and spatial-institutional fixes, embedding their spatial expansion within a China-specific policy framework; and (3) students’ learning experiences and subjectivities in Shenzhen reflect a unique “glocal” environment and a transitional space of “openness and inclusivity”. This study provides the first systematic examination of the Shenzhen case, underscoring the importance of shifting empirical focus from Anglo-American models to non-Western contexts, particularly China. I also evaluate the validity of the “learning region” within the Chinese institutional context, with a discussion of its strengths and limitations. Lastly, I discuss the use of Guanxi as a methodological tool in researching Chinese elites, emphasising the importance of socio-cultural sensitivity in qualitative research specific to context.